Αναλυτική και μοριακή χαρτογράφηση βιοσύνθεσης λυκοπενίου και αντιξειδωτικής ικανότητας εμπορικά σημαντικών ποικιλιών τομάτας - Χαλλουμά, Παντελής (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος ,Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Tomato (Solanum lycopersicum) is the second most important vegetable crop in the world after potato and undoubtedly the most popular vegetable crop since it is considered to be the most economically advantageous growing vegetable. The ripe fruit has an intense red color, because it contains the pigment lycopene, which accounts for approximately 60-74% of the total content of carotenoids in tomatoes and is considered to be the most effective antioxidant among the carotenoids through reactive oxygen species (ROS) scavenging. The antioxidant properties of lycopene contribute greatly to the fruit’s potential anticancer properties. In the current study we examined samples from three commercial tomato varieties (Hellfrucht, Brillante Fa 179 and HA34449 F1 hybrid - cherry) in three developmental/ripening stages of each fruit (immature, breaker and ripe). Using fresh tomatoes and following an analytical approach an increase in lycopene content was observed in tomatoes correlating with the transition from the immature green stage to the mature red with the highest lycopene content being quantified in the skin of tomatoes. Having focused on the red ripe stage, we determined the total antioxidant capacity with two different antioxidant capacity quantification approaches: FRAP and TEAC methods. As expected, the three varieties demonstrate lower antioxidant activity progressing from the outer layers of the fruit to the inside (highest antioxidant activity in the skin), a result strongly correlating with high lycopene content. In addition, the tomato variety with the highest lycopene content (HA34449 F1 hybrid – cherry) also demonstrated the highest antioxidant capacity. Fresh tomatoes were used for molecular analysis too, such as RNA isolation using Trizol protocol and quantification and complementary DNA (cDNA) synthesis using the reaction of reverse transcription. PCR analysis using the house-keeping gene GAPD verified the cDNA synthesis of each tested sample functioning as an indicator of high RNA quality. Furthermore, real-time RT-PCR analysis indicated the differential expression of two highly important genes (SlZDS and SlbLCY) involved in lycopene biosynthesis keeping the housekeeping gene GAPD as a reference gene.
Keywords: Sprouts; Tomatoes; Cultivation; Λάχανα; Ντομάτες; Καλλιέργεια